2006
DOI: 10.1111/j.1460-9568.2006.04891.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain cytokine synthesis induced by an intraparenchymal injection of LPS is reduced in MCP‐1‐deficient mice prior to leucocyte recruitment

Abstract: We have previously shown that ischaemic lesions are smaller in monocyte chemoattractant protein-1-deficient (MCP-1(-/-)) mice than in wild-type (wt) controls. In addition to its role as a monocyte chemoattractant, monocyte chemoattractant protein-1 (MCP-1) has been proposed to contribute to lesion progression after focal ischaemia by driving local cytokine synthesis by resident glia. To investigate this hypothesis we injected lipopolysaccharide (LPS) into the brain parenchyma of MCP-1(-/-) mice and compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 47 publications
4
50
1
2
Order By: Relevance
“…They have potent chemoattractant capability and promote monocyte recruitment into an inflammatory or pathological site. Once they were activated near the site of pathology, the recruited cells can produce more inflammatory mediators, thus inducing inflammation response [10,36]. Similarly, MCP-1 and MIP-1α in vitreous fluid from PDR patients were significantly higher than that of from control groups [37].…”
Section: Discussionmentioning
confidence: 94%
“…They have potent chemoattractant capability and promote monocyte recruitment into an inflammatory or pathological site. Once they were activated near the site of pathology, the recruited cells can produce more inflammatory mediators, thus inducing inflammation response [10,36]. Similarly, MCP-1 and MIP-1α in vitreous fluid from PDR patients were significantly higher than that of from control groups [37].…”
Section: Discussionmentioning
confidence: 94%
“…Mice that overexpress MCP-1 show increased Iba-1 immunoreactivity and accelerated senescent neurodegeneration (Yamamoto et al, 2005). Moreover, the upregulation of MCP-1 in CNS tissue can exacerbate neuronal death and other pathologies occurs before the detectable monocyte recruitment (Rankine et al, 2006), indicating that the contributions of MCP-1 to neuroinflammation are far beyond its role as a chemoattractant (Hughes et al, 2002;Rankine et al, 2006). A recent study found that trimethyltin induced hippocampal degeneration involved marked MCP-1 induction, without TNFα, IL-1, IL-6, or other proinflammatory cytokines (Little et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As a potential neurotoxin, enhanced expression of MCP-1 increases the volume of an infarct after middle cerebral artery (MCA) occlusion (Chen et al, 2003), whereas MCP-1 knockout mice have smaller infarcts and less neuronal loss compared to their wild-type controls (Hughes et al, 2002). The production of the proinflammatory cytokines such as IL-1β (interleukin-1 beta) and TNFα (tumor necrosis factor alpha) is significantly reduced in MCP-1 knockout mice challenged with LPS (lipopolysaccharide) (Rankine et al, 2006). These knockout mice also exhibit a substantial reduction in alcohol consumption and preference (Blednov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of MCP-1 and its receptor CCR2 is rapidly increased in a wide range of cell types after acute brain injury. 82,83 Astrocytes, and to a lesser extent macrophages or fully reactive microglia, have been found to express MCP-1 following ischemia 84 and mechanical injury, 81 and CCR2 colocalized with activated microglia, 85 neurons, and astrocytes. 82 In addition to monocyte recruitment, there is direct evidence for the involvement of MCP-1 in driving acute inflammatory responses within the CNS, as well as indications that it may contribute to the pathogenesis of brain lesion development.…”
Section: Monocyte Chemoattractant Proteinmentioning
confidence: 99%